2022
DOI: 10.1038/s41598-022-04859-y
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the performance of cucumber (Cucumis sativus L.) seedlings by LED illumination

Abstract: Light is one of the most important limiting factors for photosynthesis and the production of plants, especially in the regions where natural environmental conditions do not provide sufficient sunlight, and there is a great dependence on artificial lighting to grow plants and produce food. The influence of light intensity, quality, and photoperiod on photosynthetic pigments content and some biochemical and growth traits of cucumber seedlings grown under controlled conditions was investigated. An orthogonal desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 50 publications
1
15
1
Order By: Relevance
“…In another study, exposure of the leaves of lettuce plants to different R/FR LEDs altered the photochemistry of the plants. As compared to the control, which had an F V /F M value of 0.81, there occurred a reduction in the value of F V /F M , which was less than 0.8 after 11 days of treatments; the results indicate that in lettuce, R/FR exerts a stress on the plants, and this may be due to the absence of blue light [ 100 ]. The quantum yield of photosynthesis, ETR, and photochemical quenching were increased when seedlings of tomato were irradiated with a low R:FR value compared to the seedlings irradiated with a high R:FR value [ 3 ].…”
Section: Quality Of Lightmentioning
confidence: 99%
“…In another study, exposure of the leaves of lettuce plants to different R/FR LEDs altered the photochemistry of the plants. As compared to the control, which had an F V /F M value of 0.81, there occurred a reduction in the value of F V /F M , which was less than 0.8 after 11 days of treatments; the results indicate that in lettuce, R/FR exerts a stress on the plants, and this may be due to the absence of blue light [ 100 ]. The quantum yield of photosynthesis, ETR, and photochemical quenching were increased when seedlings of tomato were irradiated with a low R:FR value compared to the seedlings irradiated with a high R:FR value [ 3 ].…”
Section: Quality Of Lightmentioning
confidence: 99%
“…Rocket plants responded to LM7 in a big way, not only in terms of shoot length, but also in terms of root length and total leaf area (Figure 3). Elmardy et al (2021) found similar findings in rocket salad plants with the combination of (220 μmol m −2 s −1 ; R70:G0:B30; 10 h/14 h) and in cucumber (Cucumis sativus L.) seedlings with the combination of (150 μmol m −2 s −1 ; R70:G0:B30; 12 h/12 h) exhibited the best results for plant height and number of leaves (Hamedalla et al, 2022). When plants were grown under low light intensity (100 μmol m −2 s −1 ) and a high blue ratio (30% red/70% blue), Liang et al (2021) found that a mix of red and blue lights was beneficial to plant height, total leaf area, and root length of passion fruit seedlings.…”
Section: Discussionmentioning
confidence: 53%
“…Light is one of the most important factors responsible for plant development and growth (Wassink and Stolwijk, 1956). Previous research has shown that changing light intensity, quality, and photoperiod may alter growth and govern developmental transitions (Meng et al, 2020;Elmardy et al, 2021;Liang et al, 2021;Hamedalla et al, 2022;Malekzadeh Shamsabad et al, 2022). Basic plant research using various light spectrums has shown that well-defined light wavelengths have a significant impact on plant physiology such as germination and stem development (Parks et al, 2001), biomass and flowering transition (Valverde et al, 2004), in the outcome of plant-pathogen interactions (Meng et al, 2020) and an increase in plant resilience under stress conditions (Malekzadeh Shamsabad et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An orthogonal design was used to obtain the optimal experimental conditions in iodine adsorption [ 49 ]. An orthogonal design was used to optimize light irradiance and the ratio of photoperiods and LEDs in order to increase the photosynthetic capacity and growth of cucumber seedlings by LED illumination [ 50 ].…”
Section: Resultsmentioning
confidence: 99%